Pengaruh Tata Kelola Perusahaan dan Kualitas Auditor terhadap Manajemen Laba pada Bank Umum Syariah di Indonesia - Triana Novitasari; Nur Hisamuddin; Bunga Maharani (Universitas Jember, 2019)
The aimed of this research was to examine the influence of corporate governance and auditor quality on earnings management in islamic banks in Indonesia. Corporate governance in this research used the size of audit committee, the size of Shariah Supervisory Board and managerial ownership as a proxy. Auditor quality in this research used accountant firm size as a proxy. The type of this research was explanatory research. The population were islamic banks listed in Bank Indonesia during 2013-2018. Using purposive sampling method, the sample were 60 islamic banks in Indonesia. Data resource using annual report from each islamic banks. The analysis method using multiple linear regression. The result indicated that managerial ownership had positive influence on earnings management, meanwhile the size of audit committee, the size of SSB, and auditor quality had no influence on earnings management. Keywords: auditor quality, corporate governance, earnings management, islamic banks